1998
DOI: 10.1109/68.701536
|View full text |Cite
|
Sign up to set email alerts
|

A novel optical decision circuit based on a Mach-Zehnder or Michelson interferometer and gain-clamped semiconductor optical amplifiers

Abstract: Abstract-A novel optical decision circuit based on a MachZehnder or Michelson interferometer with a gain-clamped semiconductor optical amplifier in each arm is proposed. Simulation results show that the component, of which the decision threshold can easily be modified through adjustment of the currents in both amplifiers, exhibits excellent reshaping capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In [6], it was found that the relaxation oscillations occurring during the on-and off-switching of the laser mode in the GCSOAs seriously affect the transient behavior of the regenerator. This on-and off-switching corresponds with the amplifier going out and into saturation.…”
Section: Experimental Characteristics Of the Regeneratormentioning
confidence: 99%
See 3 more Smart Citations
“…In [6], it was found that the relaxation oscillations occurring during the on-and off-switching of the laser mode in the GCSOAs seriously affect the transient behavior of the regenerator. This on-and off-switching corresponds with the amplifier going out and into saturation.…”
Section: Experimental Characteristics Of the Regeneratormentioning
confidence: 99%
“…This on-and off-switching corresponds with the amplifier going out and into saturation. Time domain simulations, shown in [6], indicated that the maximum bitrate was limited to about 3 Gbit/s. Preliminary measurements of the dynamic behavior of a single GCSOA, with an input consisting of periodic pulses driving the amplifier into saturation, confirm this prediction.…”
Section: Experimental Characteristics Of the Regeneratormentioning
confidence: 99%
See 2 more Smart Citations
“…The laser model also offered the possibility of injecting signals at both facets. The material parameters were chosen as in [19]. The dimensions together with the gain suppression factor are given in Table II.…”
Section: Models Used For Simulationsmentioning
confidence: 99%